First confirmation of variegated molehopper Xya variegata (Latreille, 1809) (Orthoptera: Tridactylidae) occuring in Slovenia - Bedjanič, Matjaž (Natura Sloveniae, 2023)
The occurrence of the variegated molehopper Xya variegata in Slovenia is confirmed unambiguously for the first time, based on observations of adults and larvae on 24. 3. 2023 and 2. 6. 2023 on the banks of a gravel pit along the Mura River, east of Petišovci in the Prekmurje region, northeastern Slovenia. Thus, the previously doubtful inclusion of the species in the checklist of Slovenian Orthoptera is now justified. Further research is needed to improve knowledge of its distribution and biology. A detailed assessment of the threat status and planning of conservation measures for this threatened and ecologically highly specialised grasshopper species should also be carried out.
Keywords: Caelifera; distribution; grasshoppers; kobilice; kratkotipalčnice; ogroženost; Orthoptera; razširjenost; Slovenia; Slovenija; threat status; Xya; zoologija; zoology